The San Saturnino Basilica (Cagliari, Italy): An Up-Close Investigation about the Archaeological Stratigraphy of Mortars from the Roman to the Middle Ages - Sitzia, Fabio (2022)
The manufacturing technology of historical mortars from the Roman to Medieval period apparently has not undergone evolutions. As reported in the literature, a quality decrease in the raw material occurred after the fall of the Roman Empire. During the Roman Age, the mortars presented the requirements of long durability due to hydraulic characteristics, and in later times, the production has only partially maintained the ancient requirements. To focus on the different production technologies between Roman and Medieval mortar, this research presents the case study of San Saturnino Basilica (Italy), where an archaeological mortar stratigraphy from Roman to Middle Ages is well preserved. An archaeometric characterization was performed to compare the mortars of the Roman period with the mortars of the Medieval period collected from the case-study monument. This comparison was carried out by measuring some physical-mechanical, mineralogical, petrographic and thermal features that give more information about the durability and resistance to mechanical solicitations and weathering. After the characterizations, contrary to what is reported in the bibliography, a better quality of Medieval materials than Roman ones is pointed out. This has been highlighted by higher hydraulicity, mechanical performance, and a more appropriated particle-size distribution of aggregates.